Gestión de los Activos Fijos del Gobierno Autónomo Descentralizado de la Provincia de Cotopaxi, una Aproximación Interpretativa - Negrete Panchi, Alexandra Clementina (2023)
The objective of this project was to structure an internal control proposal for the administration of fixed assets of the Decentralized Autonomous Government of the province of Cotopaxi, through the theoretical foundation of the management of fixed assets in public administration, the description of the current situation of the management of fixed assets in the entity and the establishment of those responsible for the administration of fixed assets for the optimization in their use, management and control. The bibliography analyzed inherent to the subject is related to the Ecuadorian context. The research methodology had a qualitative approach of a descriptive - documentary type, the method was inductive and the technique corresponded to the interview with the personnel that works in the Fixed Assets Unit, for the analysis of the data the MAXQDA software was used, which allowed find links between the answers and thus, conclude that the management of fixed assets is inadequate, there is no control proposal that governs the interior of the entity and the ignorance of the custodians about the duties and rights they have prevails. From which, the proposal was generated in coherence with the related regulations, which will support the management of fixed assets in the Prefecture.